Maternal selenium deficiency was positively associated with the risk of selenium deficiency in children aged 6-59 months in rural Zimbabwe. - Beaula Mutonhodza; Muneta G Manzeke-Kangara; Elizabeth H Bailey; Tonderayi M Matsungo; Prosper Chopera (Public Library of Science (PLoS), 2024)
There is growing evidence showing the existence of selenium (Se) deficiency among women and children in sub-Saharan Africa. Unfortunately, the key drivers of Se deficiency are not clearly understood. This study assessed the determinants of Se deficiency among children aged 6-59 months and Women of Reproductive Age (WRA), in Zimbabwe. This cross-sectional biomarker study was conducted in selected districts in rural Zimbabwe (Murewa, Shamva, and Mutasa). Children aged 6-59 months (n = 683) and WRA (n = 683), were selected using a systematic random sampling approach. Venous blood samples were collected, processed, and stored according to World Health Organization (WHO) guidelines. Plasma selenium concentration was measured using inductively coupled plasma-mass spectrometry (ICP-MS). Anthropometric indices were assessed and classified based on WHO standards. Demographic characteristics were adapted from the Zimbabwe Demographic Health Survey standard questionnaire. Multiple logistic regression analysis showed that children whose mothers were Se deficient were 4 times more likely to be Se deficient compared to those whose mothers were Se adequate (OR = 4.25; 95% CI; 1.55-11.67; p = 0.005). Girl children were 3 times more likely to be Se deficient compared to boys (OR = 2.84; 95% CI; 1.08-7.51; p = 0.035). Women producing maize for consumption were 0.5 times more likely to be Se deficient than non-producers (OR = 0.47; 95% CI; 0.25-0.90; p = 0.022). The risk of Se depletion in children was amplified by maternal deficiency. Therefore, initiation of maternal multiple micronutrient supplementation from preconception through lactation is beneficial to both children and women.